Cybercrime and Its Impact on E-Commerce Technology - Harahap, Efni Yulia Santri; Ramadhani, Nabila; Nurbaiti, Nurbaiti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study aims to educate those who use e-commerce about the existence of cybercrime and its impact on e-commerce applications. Cybercrime is known as a cyber crime that is carried out online. One example of this is e-commerce. Those who use e-commerce already know about the effects of cybercrime on e-commerce. Predicting cybercrime remains difficult. So should be more vigilant against this crime.